Use of a new external fixator for the correction of fixed flexion deformity of the fingers - Siow, Y.S.; Ahmad, T.S.; Goh, S.Y. (World Scientific Publishing, 1999)
Three patients with severe fixed flexion deformity of the fingers caused by trauma were reported. As an alternative treatment, a new mini external fixator was used to correct the deformities. The use of this device has made treatment of contractures simpler and more predictable. Gradual distraction and straightening was applied to loosen and extend the joints, followed by a period of mobilisation while still on the device. In all the three patients, this experimental device and approach led to improvement of the fixed flexion deformities. With use of this device, surgical release may not be necessary.